Parameterizing ice nucleation rates using contact angle and activation energy derived from laboratory data - J.-P. Chen; A. Hazra; Z. Levin (Atmospheric Chemistry and Physics, 2008)
The rate of ice nucleation in clouds is not easily determined and large discrepancies exist between model predictions and actual ice crystal concentration measured in clouds. In an effort to improve the parameterization of ice nucleating in cloud models, we investigate the rate of heterogeneous ice nucleation under specific ambient conditions by knowing the sizes as well as two thermodynamic parameters of the ice nuclei – contact angle and activation energy. Laboratory data of freezing and deposition nucleation modes were analyzed to derive inversely the two thermodynamic parameters for a variety of ice nuclei, including mineral dusts, bacteria, pollens, and soot particles. The analysis considered the Zeldovich factor for the adjustment of ice germ formation, as well as the solute and curvature effects on surface tension; the latter effects have strong influence on the contact angle. Contact angle turns out to be a more important factor than the activation energy in discriminating the nucleation capabilities of various ice nuclei species. By extracting these thermodynamic parameters, laboratory results can be converted into a formulation that follows classical nucleation theory, which then has the flexibility of incorporating factors such as the solute effect and curvature effect that were not considered in the experiments. Due to various uncertainties, contact angle and activation energy derived in this study should be regarded as "apparent" thermodynamics parameters.